UFO: an Arabidopsis gene involved in both floral meristem and floral organ development. - Levin, J Z (1995)
We describe the role of the UNUSUAL FLORAL ORGANS (UFO) gene in Arabidopsis floral development based on a genetic and molecular characterization of the phenotypes of nine ufo alleles. UFO is required for the proper identity of the floral meristem and acts in three different aspects of the process that distinguishes flowers from shoots. UFO is involved in establishing the whorled pattern of floral organs, controlling the determinacy of the floral meristem, and activating the APETALA3 and PISTILLATA genes required for petal and stamen identity. In many respects, UFO acts in a manner similar to LEAFY, but the ufo mutant phenotype also suggests an additional role for UFO in defining boundaries within the floral primordia or controlling cell proliferation during floral organ growth. Finally, genetic interactions that prevent flower formation and lead to the generation of filamentous structures implicate UFO as a member of a new, large, and diverse class of genes in Arabidopsis necessary for flower formation.